Preparation method and application of aerogel composite foamed silica gel cotton with low thermal conductivity
Patent Information
- Application Number
- CN202611328501.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-13
AI Technical Summary
其中,纯气凝胶毡孔隙率高、导热系数低,但存在力学强度差、脆性大、易粉化掉渣、无法折弯成型、不能加工异形孔位的缺陷,装配使用后极易失效,不具备结构密封件的使用价值
1、本发明制备的低导热率的气凝胶复合发泡硅胶棉,具有超低导热的特性,隔热性能优异。产品室温导热系数≤0.045W/(m·K),120℃高温导热系数≤0.060W/(m·K),相较传统发泡硅胶隔热性能提升60%以上,可高效阻隔热传导、抑制电池热失控扩散,适配高端储能设备高温隔热防护需求。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of silicone foam materials, specifically relating to a method for preparing and applying aerogel composite foamed silicone cotton with low thermal conductivity. Background Technology
[0002] Silicone foam possesses excellent resistance to high and low temperatures, high elasticity, insulation, heat insulation, and cushioning and sealing properties, making it a core sealing and insulation material in the new energy field. However, with the continuous upgrading of safety standards in the power battery and energy storage industries, the performance shortcomings of traditional silicone foam materials are becoming increasingly apparent.
[0003] Existing conventional foamed silicone materials generally have a room temperature thermal conductivity of 0.12–0.18 W / (m·K). Their thermal conductivity increases significantly at high temperatures, resulting in weak ability to prevent and suppress battery thermal runaway, failing to meet the fireproof and thermal insulation safety requirements of high-end energy storage devices. Furthermore, ordinary foamed silicone exhibits large compression set and significant rebound attenuation after long-term high and low temperature cycling, leading to a substantial decrease in sealing reliability. Conventional products only achieve a UL94-V1 flame retardant rating, making it difficult to meet the stringent fireproof and flame retardant standards for power batteries.
[0004] To reduce the thermal conductivity of materials, existing technologies mostly employ pure aerogel felt or simple doping and modification schemes using aerogel powder. Pure aerogel felt has high porosity and low thermal conductivity, but suffers from poor mechanical strength, brittleness, easy powdering and flaking, inability to bend and shape, and inability to process irregularly shaped pores. It is prone to failure after assembly and use, and therefore lacks the value of a structural sealing component. Traditional aerogel-silicone rubber composite processes are merely simple physical blending; the aerogel powder easily agglomerates and accumulates, forming numerous defects and heat conduction channels within the rubber matrix. This not only fails to effectively reduce thermal conductivity but also disrupts foaming uniformity, leading to a decrease in material closed-cell rate, deterioration of compression and resilience performance, reduced mechanical strength, low mass production yield, and substandard long-term durability.
[0005] In addition, existing composite foamed silicone generally suffers from problems such as uneven foam pore size, poor density consistency, easy bubbling and lifting of the adhesive backing, and high rebound loss rate after humid heat aging. It cannot simultaneously achieve the integrated performance of ultra-low thermal conductivity, high resilience, halogen-free flame retardancy, high-level waterproofing, and long-term weather resistance and durability, which seriously restricts the iterative upgrading and large-scale application of high-end sealing and heat insulation materials for new energy. Summary of the Invention
[0006] This invention addresses the shortcomings of existing technologies by providing a method for preparing and applying aerogel composite foamed silicone cotton with low thermal conductivity, solving the problem of aerogel agglomeration and constructing a uniform and dense microporous thermal insulation structure.
[0007] To solve the above-mentioned technical problems, the objective of this invention is achieved through the following technical solution: A method for preparing aerogel composite foamed silicone cotton with low thermal conductivity includes the following steps: (1) Surface grafting modification of hydrophobic silica aerogel powder: The hydrophobic silica aerogel powder was mixed with γ-(2,3-epoxypropoxy)propyltrimethoxysilane diluted with anhydrous ethanol, stirred at 50-70℃ for 40-80 min, and then dried at 90-110℃ for 1.5-2.5 h to obtain modified aerogel powder; (2) Preparation of component A: By mass, 70-80 parts of vinyl polysiloxane, 20-30 parts of low viscosity vinyl silicone oil, 15-35 parts of modified aerogel powder prepared in step (1), 8-15 parts of reinforcing filler, 20-40 parts of flame retardant filler, and 2-5 parts of structuring control agent are mixed and kneaded evenly below 70°C. After cooling to below 40°C, 0.1-0.3 parts of platinum catalyst and 3-6 parts of microcapsule foaming agent are added and mixed evenly to obtain component A. (3) Preparation of component B: By mass, 25-40 parts of hydrogen-containing silicone oil, 10-20 parts of modified aerogel powder prepared in step (1), 15-30 parts of flame-retardant filler, and 0.05-0.2 parts of reaction inhibitor are mixed and dispersed evenly to obtain component B; (4) Mix component A and component B in equal mass ratio, degas at a vacuum of -0.09 to -0.1 MPa for 5 to 8 minutes, and then inject into a mold. Mold and foam vulcanize at 115 to 125°C and 8 to 12 MPa for 15 to 20 minutes. The decomposition temperature of the microcapsule foaming agent is 110 to 130°C, and the difference between the decomposition temperature of the microcapsule foaming agent and the temperature of the molding and foaming vulcanization does not exceed 5°C.
[0008] As a further improvement of the present invention, the molding foaming vulcanization is carried out in a four-section temperature-controlled mold, with each temperature zone independently controlled. The mold is equipped with a micro-overflow groove to balance the foaming pressure.
[0009] As a further improvement of the present invention, the hydrophobic silica aerogel powder has a particle size of 5-15 μm and a specific surface area of 600-800 m². 2 / g, thermal conductivity ≤0.022 W / (m·K).
[0010] As a further improvement of the present invention, the reinforcing filler is fumed silica, the flame retardant filler is aluminum hydroxide, the structuring control agent is hydroxyl silicone oil, and the reaction inhibitor is ethynylcyclohexanol.
[0011] As a further improvement of the present invention, the molecular weight of the vinyl polysiloxane is 500,000 to 700,000, the viscosity of the low-viscosity vinyl silicone oil is 100 to 1000 mPa·s, and the active hydrogen content of the hydrogen-containing silicone oil is 1.0% to 1.5%.
[0012] As a further improvement of the present invention, after the vulcanization is completed, the semi-finished product is placed in a shaping fixture and kept at a constant temperature for 1.5 to 3 hours to eliminate the internal stress of molding.
[0013] As a further improvement of the present invention, both the reinforcing filler and the flame-retardant filler are subjected to hydrophobic modification treatment.
[0014] This invention also provides an application of aerogel composite foamed silicone cotton with low thermal conductivity, which is prepared by the above method and is used as a heat insulation and sealing material in power battery PACKs, energy storage cabinets or new energy electrical equipment.
[0015] The core technical principle and mechanism of this invention are as follows: This invention employs in-situ grafting modification and dispersion technology for aerogel. Specifically, this invention uses KH-560 silane coupling agent to pretreat aerogel powder, grafting organic functional groups onto the powder surface. This significantly improves the interfacial compatibility and bonding force between the aerogel and the silicone rubber organic matrix, achieving micron-level uniform dispersion of the aerogel powder. This completely solves the pain points of powder agglomeration and internal thermal bridging in traditional processes, maximizing the preservation of the aerogel's ultra-low thermal conductivity while not damaging the elasticity and mechanical properties of the silicone substrate.
[0016] This invention employs a controllable composite foaming system with precise temperature zone matching. Specifically, it selects a microcapsule composite foaming agent whose decomposition temperature is highly matched with the vulcanization temperature of silicone rubber, and combines it with a four-stage zoned temperature-controlled molding process to precisely control the foaming rate and vulcanization rate to proceed simultaneously, forming a uniform microporous structure with a pore size of 100-300μm. The product has a closed-cell rate of ≥92%, and synergistically achieves multiple properties such as ultra-low thermal conductivity, high resilience, and dense waterproofing, breaking through the technical bottlenecks of uneven foaming, bubble collapse, and rapid rebound decay of traditional composite materials.
[0017] This invention employs a post-molding stress-setting process. Specifically, it adds a dedicated constant-temperature tooling setting process to effectively release the internal stress of vulcanization molding, solving the mass production problems of large-size, L-shaped irregular foam silicone cotton after demolding, such as twisting and warping, hole position misalignment, and dimensional deviation. This significantly improves the processing accuracy and mass production yield of irregular structures and multi-hole precision parts.
[0018] This invention establishes an integrated synergistic system for heat insulation, flame retardancy, durability, and waterproofing. Specifically, it constructs a synergistic functional system of aerogel heat insulation reinforcement and halogen-free flame retardancy of aluminum hydroxide, combined with a low-deformation silicone substrate formulation. Without additional modification, it can simultaneously achieve integrated performance of ultra-low thermal conductivity, UL94-V0 halogen-free flame retardancy, low compression set, high weather resistance, and IP68 high-level waterproofing. Its comprehensive performance is significantly better than existing commercial products of the same type.
[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The aerogel composite foamed silicone cotton with low thermal conductivity prepared by this invention has ultra-low thermal conductivity and excellent thermal insulation performance. The product has a room temperature thermal conductivity ≤0.045W / (m·K) and a high temperature thermal conductivity ≤0.060W / (m·K) at 120℃, which is more than 60% better than the thermal insulation performance of traditional foamed silicone. It can effectively block heat conduction and suppress the spread of battery thermal runaway, and is suitable for the high temperature thermal insulation protection requirements of high-end energy storage equipment.
[0020] 2. The aerogel composite foamed silicone cotton with low thermal conductivity prepared by this invention exhibits low deformation, high resilience, and strong sealing stability. The product density is controlled between 0.38 and 0.42 g / cm³. 3 Under 100℃ / 24h conditions, the compression set is ≤4.8%; after 500 cycles of high and low temperatures from -40℃ to 85℃, the compression set is ≤9%; after 1000h of damp heat aging at 85℃ and 85%RH, the rebound loss is ≤28%. It exhibits stable sealing performance over long-term service and excellent anti-aging and anti-fading capabilities. Furthermore, the high closed-cell microporous structure (≥92%) combined with a seamless, one-piece molding process achieves an IP68 waterproof rating, with no bubbles, wrinkles, or lifting during adhesive bonding. Long-term use ensures stable sealing performance and excellent anti-aging and anti-fading capabilities.
[0021] 3. The low thermal conductivity aerogel composite foamed silicone cotton prepared by this invention is halogen-free and flame-retardant, with reliable electrical safety. The product achieves the highest halogen-free flame-retardant rating of UL94-V0, exhibiting no dripping or release of toxic or harmful fumes during high-temperature combustion, meeting the stringent fire safety standards for new energy batteries. The silicone rubber matrix and high closed-cell structure endow the material with excellent electrical insulation properties, making it suitable for heat insulation and sealing applications in high-voltage electrical equipment. Detailed Implementation
[0022] The present invention will be further described in detail below with reference to embodiments, but the implementation of the present invention is not limited thereto.
[0023] Example 1 Formula composition (parts by weight): Component A: 75 parts vinyl polysiloxane (110# silicone rubber raw rubber, molecular weight 600,000), 25 parts low viscosity vinyl silicone oil, 25 parts modified aerogel powder, 12 parts fumed silica (2500 mesh), 30 parts aluminum hydroxide, 3 parts hydroxyl silicone oil, 0.2 parts platinum catalyst (3000ppm platinum water), 4 parts microcapsule foaming agent, 2 parts gray inorganic pigment, and 1 part KH-560 silane coupling agent.
[0024] Component B: 32 parts of hydrogen-containing silicone oil (1.2% hydrogen content), 15 parts of modified aerogel powder, 22 parts of aluminum hydroxide, and 0.1 parts of ethynylcyclohexanol.
[0025] Preparation process: Step 1 (Surface Modification Pretreatment of Aerogel Powder): Hydrophobic silica aerogel powder (particle size 5–15 μm, specific surface area 600–800 m²) is prepared. 2 / g, with a native thermal conductivity ≤0.022W / (m·K)) is fed into a high-speed dispersion device, and KH-560 silane coupling agent diluted with anhydrous ethanol (1% of the mass of the aerogel powder) is added. The mixture is stirred at a constant temperature of 60℃ for 60 min to allow the coupling agent molecules to fully graft the active hydroxyl groups on the aerogel surface. After grafting, the powder is placed in an environment of 100℃ and dried for 2 h to completely remove the ethanol solvent, thereby obtaining highly dispersed modified aerogel powder.
[0026] Step 2 (Preparation of Component A through mixing): Add 75 parts of vinyl polysiloxane and 25 parts of low-viscosity vinyl silicone oil to a kneader and premix at room temperature for 20 minutes to soften the compound and reduce the viscosity of the system. Add 25 parts of modified aerogel powder, 12 parts of fumed silica, and 30 parts of aluminum hydroxide in 3 batches, strictly controlling the mixing temperature of each batch to ≤70℃ and kneading at a constant temperature for 40 minutes to ensure uniform wetting and dispersion of the powder without agglomeration. Then add 3 parts of hydroxyl silicone oil, 4 parts of microcapsule foaming agent, and 2 parts of gray inorganic pigment paste, stir evenly, and cool down to below 40℃. Finally, add 0.2 parts of platinum-based catalyst at low temperature and low speed, stir for 15 minutes, and seal and store in the dark after discharge.
[0027] Step 3 (Preparation of Component B by mixing): At room temperature, add 32 parts of hydrogen-containing silicone oil, 15 parts of modified aerogel powder, and 22 parts of aluminum hydroxide to a mixing tank and disperse at high speed for 30 minutes until the system is uniform and free of particles; add 0.1 parts of ethynylcyclohexanol, stir at low speed for 10 minutes, filter to remove trace impurities, seal and store at room temperature for later use.
[0028] Step 4 (Vacuum Mixing and Degassing): Mix component A and component B thoroughly in equal mass ratio, and degas under vacuum for 6 minutes, with the vacuum level controlled at -0.095 MPa.
[0029] Step 5 (Zone-zone temperature-controlled molding foaming vulcanization): The defoamed mixture is put into a four-section zone temperature-controlled mold. The overall temperature of the mold is controlled at 120℃, the molding pressure is 10MPa, and the heat and pressure are maintained for 18 minutes. The temperature difference of the large mold is balanced by multi-zone independent temperature control, and the foaming pressure is balanced by the micro-overflow groove structure of the mold.
[0030] Step Six (Constant Temperature Stress Shaping Treatment): After the semi-finished product is removed from the vulcanization molding process, it is immediately placed into a special shaping fixture and kept at a constant temperature for 2 hours to completely eliminate the internal stress of vulcanization molding.
[0031] Step 7 (Post-processing and Packaging): After shaping, pre-set round holes and waist holes are processed using CNC punching equipment, and all hole edges are rounded and deburred; double-sided adhesive is applied using fully automatic roller pressing equipment; finally, a protective film is applied, and each piece is individually blister packaged to complete the finished product preparation.
[0032] Example 2 Formula composition (parts by weight): Component A: 72 parts vinyl polysiloxane (110# silicone rubber raw rubber, molecular weight 600,000), 22 parts low viscosity vinyl silicone oil, 32 parts modified aerogel powder, 10 parts fumed silica (2500 mesh), 28 parts aluminum hydroxide, 3 parts hydroxyl silicone oil, 0.2 parts platinum catalyst (3000ppm platinum water), 4 parts microcapsule foaming agent, 2 parts gray inorganic pigment, and 1.2 parts KH-560 silane coupling agent.
[0033] Component B: 30 parts of hydrogen-containing silicone oil (1.2% hydrogen content), 18 parts of modified aerogel powder, 20 parts of aluminum hydroxide, and 0.1 parts of ethynylcyclohexanol.
[0034] Preparation process: Step 1 (Surface Modification Pretreatment of Aerogel Powder): Hydrophobic silica aerogel powder (particle size 5–15 μm, specific surface area 600–800 m²) is prepared. 2 / g, with a native thermal conductivity ≤0.022W / (m·K)) was fed into a high-speed dispersion device, and KH-560 silane coupling agent diluted with anhydrous ethanol (1.2% of the mass of the aerogel powder) was added. The mixture was stirred at a constant temperature of 65℃ for 70 min to allow the coupling agent molecules to fully graft the active hydroxyl groups on the aerogel surface. After grafting, the powder was placed in an environment of 105℃ and dried for 2 h to completely remove the ethanol solvent and obtain highly dispersed modified aerogel powder.
[0035] Step 2 (Preparation of Component A through mixing): Add 72 parts of vinyl polysiloxane and 22 parts of low-viscosity vinyl silicone oil to a kneader and premix at room temperature for 20 minutes to soften the compound and reduce the viscosity of the system. Add 32 parts of modified aerogel powder, 10 parts of fumed silica, and 28 parts of aluminum hydroxide in 3 batches. Strictly control the mixing temperature of each batch to ≤70℃ and knead at a constant temperature for 45 minutes to ensure uniform wetting and dispersion of the powder without agglomeration. Then add 3 parts of hydroxyl silicone oil, 4 parts of microcapsule foaming agent, and 2 parts of gray inorganic pigment paste. After stirring evenly, cool down to below 40℃. Finally, add 0.2 parts of platinum catalyst at low temperature and low speed and stir for 15 minutes. After discharge, seal and store in the dark.
[0036] Step 3 (Preparation of Component B by mixing): At room temperature, add 30 parts of hydrogen-containing silicone oil, 18 parts of modified aerogel powder, and 20 parts of aluminum hydroxide to a mixing tank and disperse at high speed for 30 minutes until the system is uniform and free of particles; add 0.1 parts of ethynylcyclohexanol, stir at low speed for 10 minutes, filter to remove trace impurities, seal and store at room temperature for later use.
[0037] Step 4 (Vacuum Mixing and Degassing): Mix component A and component B thoroughly in equal mass ratio, and place in a vacuum environment for degassing for 7 minutes, with the vacuum degree controlled at -0.098MPa.
[0038] Step 5 (Zone-zone temperature-controlled molding foaming vulcanization): The degassed mixture is put into a four-section zone temperature-controlled mold. The overall temperature of the mold is controlled at 122℃, the molding pressure is 10MPa, and the heat and pressure are maintained for 20 minutes. The temperature difference of the large mold is balanced by multi-zone independent temperature control, and the foaming pressure is balanced by the micro-overflow groove structure of the mold.
[0039] Step Six (Constant Temperature Stress Shaping Treatment): After the semi-finished product is removed from the vulcanization molding process, it is immediately placed into a special shaping fixture and kept at a constant temperature for 2.5 hours to completely eliminate the internal stress of vulcanization molding.
[0040] Step 7 (Post-processing and Packaging): After shaping, pre-set round holes and waist holes are processed using CNC punching equipment, and all hole edges are rounded and deburred; double-sided adhesive is applied using fully automatic roller pressing equipment; finally, a protective film is applied, and each piece is individually blister packaged to complete the finished product preparation.
[0041] Example 3 Formula composition (parts by weight): Component A: 78 parts vinyl polysiloxane (110# silicone rubber raw rubber, molecular weight 600,000), 28 parts low viscosity vinyl silicone oil, 18 parts modified aerogel powder, 14 parts fumed silica (2500 mesh), 38 parts aluminum hydroxide, 4 parts hydroxyl silicone oil, 0.25 parts platinum catalyst (3000ppm platinum water), 5 parts microcapsule foaming agent, 2 parts gray inorganic pigment, and 1.5 parts KH-560 silane coupling agent.
[0042] Component B: 35 parts of hydrogen-containing silicone oil (1.2% hydrogen content), 12 parts of modified aerogel powder, 28 parts of aluminum hydroxide, and 0.15 parts of ethynylcyclohexanol.
[0043] Preparation process: Step 1 (Surface Modification Pretreatment of Aerogel Powder): Hydrophobic silica aerogel powder (particle size 5–15 μm, specific surface area 600–800 m²) is prepared. 2 / g, with a native thermal conductivity ≤0.022W / (m·K)) was added to a high-speed dispersion device, and KH-560 silane coupling agent diluted with anhydrous ethanol (1.5% of the mass of the aerogel powder) was added. The mixture was stirred at a constant temperature of 55℃ for 50 min to allow the coupling agent molecules to fully graft the active hydroxyl groups on the aerogel surface. After grafting, the powder was placed in a constant temperature environment of 95℃ and dried for 2 h to completely remove the ethanol solvent and obtain highly dispersed modified aerogel powder.
[0044] Step 2 (Preparation of Component A through mixing): Add 78 parts of vinyl polysiloxane and 28 parts of low-viscosity vinyl silicone oil to a kneader and premix at room temperature for 20 minutes to soften the compound and reduce the viscosity of the system. Add 18 parts of modified aerogel powder, 14 parts of fumed silica, and 38 parts of aluminum hydroxide in 3 batches. Strictly control the mixing temperature of each batch to ≤70℃ and knead at a constant temperature for 35 minutes to ensure uniform wetting and dispersion of the powder without agglomeration. Then add 4 parts of hydroxyl silicone oil, 5 parts of microcapsule foaming agent, and 2 parts of gray inorganic pigment paste. After stirring evenly, cool down to below 40℃. Finally, add 0.25 parts of platinum-based catalyst at low temperature and low speed, stir for 15 minutes, and seal and store in the dark after discharge.
[0045] Step 3 (Preparation of Component B by mixing): At room temperature, add 35 parts of hydrogen-containing silicone oil, 12 parts of modified aerogel powder, and 28 parts of aluminum hydroxide to a mixing tank and disperse at high speed for 30 minutes until the system is uniform and free of particles; add 0.15 parts of ethynylcyclohexanol, stir at low speed for 10 minutes, filter to remove trace impurities, seal and store at room temperature for later use.
[0046] Step 4 (Vacuum Mixing and Degassing): Mix component A and component B in equal mass ratio, and degas under vacuum for 5 minutes, with the vacuum level controlled at -0.092 MPa.
[0047] Step 5 (Zone-zone temperature-controlled molding foaming vulcanization): The degassed mixture is put into a four-section zone temperature-controlled mold. The overall temperature of the mold is controlled at 125℃, the molding pressure is 10MPa, and the heat and pressure are maintained for 16 minutes. The temperature difference of the large mold is balanced by multi-zone independent temperature control, and the foaming pressure is balanced by the micro overflow groove structure of the mold.
[0048] Step Six (Constant Temperature Stress Shaping Treatment): After the semi-finished product is removed from the vulcanization molding process, it is immediately placed into a special shaping fixture and kept at a constant temperature for 2 hours to completely eliminate the internal stress of vulcanization molding.
[0049] Step 7 (Post-processing and Packaging): After shaping, pre-set round holes and waist holes are processed using CNC punching equipment, and all hole edges are rounded and deburred; double-sided adhesive is applied using fully automatic roller pressing equipment; finally, a protective film is applied, and each piece is individually blister packaged to complete the finished product preparation.
[0050] The key performance test data of the finished products of each embodiment are as follows: Table 1 Performance Test Results Example 1 uses a moderate aerogel filling amount (25 parts of component A and 15 parts of component B). The product has a room temperature thermal conductivity of 0.042 W / (m·K), a closed-cell rate of 93.5%, and a compression set of 4.2%, exhibiting excellent and balanced performance across all aspects. Example 2, by increasing the aerogel filling amount (32 parts of component A and 18 parts of component B), reduces the thermal conductivity to 0.038 W / (m·K) and increases the closed-cell rate to 94.1%, verifying the effectiveness of the modification technology with a high aerogel filling amount. Example 3, by reducing the aerogel amount and increasing the flame-retardant filler amount, maintains the thermal conductivity at 0.044 W / (m·K) and further reduces the compression set to 3.8%, demonstrating that the formulation system of this invention has a wide range of raw material ratio adaptability and excellent overall performance control space. All three embodiments achieved a UL94 V-0 flame retardancy rating and an IP68 waterproof rating, with a rebound loss of no more than 28% after damp heat aging, indicating that the product of this invention exhibits good consistency in key performance aspects such as flame retardancy, waterproofing, and aging resistance. In summary, this invention, through the synergistic effect of core technologies such as aerogel surface modification, two-component formulation design, precise matching of microencapsulated foaming agent and vulcanization temperature, and isothermal stress setting, achieves a comprehensive advantage across a wide range of formulations, including ultra-low thermal conductivity, high closed-cell ratio, low compression set, halogen-free flame retardancy, IP68 waterproofing, and excellent aging resistance.
[0051] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, all equivalent changes made in accordance with the structure, shape, and principle of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing aerogel composite foamed silicone cotton with low thermal conductivity, characterized in that, Includes the following steps: (1) Surface grafting modification of hydrophobic silica aerogel powder: The hydrophobic silica aerogel powder was mixed with γ-(2,3-epoxypropoxy)propyltrimethoxysilane diluted with anhydrous ethanol, stirred at 50-70℃ for 40-80 min, and then dried at 90-110℃ for 1.5-2.5 h to obtain modified aerogel powder; (2) Preparation of component A: By mass, 70-80 parts of vinyl polysiloxane, 20-30 parts of low viscosity vinyl silicone oil, 15-35 parts of modified aerogel powder prepared in step (1), 8-15 parts of reinforcing filler, 20-40 parts of flame retardant filler, and 2-5 parts of structuring control agent are mixed and kneaded evenly below 70°C. After cooling to below 40°C, 0.1-0.3 parts of platinum catalyst and 3-6 parts of microcapsule foaming agent are added and mixed evenly to obtain component A. (3) Preparation of component B: By mass, 25-40 parts of hydrogen-containing silicone oil, 10-20 parts of modified aerogel powder prepared in step (1), 15-30 parts of flame-retardant filler, and 0.05-0.2 parts of reaction inhibitor are mixed and dispersed evenly to obtain component B; (4) Mix component A and component B in equal mass ratio, degas at a vacuum of -0.09 to -0.1 MPa for 5 to 8 minutes, and then inject into a mold. Mold and foam vulcanize at 115 to 125°C and 8 to 12 MPa for 15 to 20 minutes. The decomposition temperature of the microcapsule foaming agent is 110 to 130°C, and the difference between the decomposition temperature of the microcapsule foaming agent and the temperature of the molding and foaming vulcanization does not exceed 5°C.
2. The method for preparing a low thermal conductivity aerogel composite foamed silicone cotton according to claim 1, characterized in that, The molding and foaming vulcanization is carried out in a four-section temperature-controlled mold, with each temperature zone independently controlled. The mold is equipped with a micro-overflow groove to balance the foaming pressure.
3. The method for preparing a low thermal conductivity aerogel composite foamed silicone cotton according to claim 1, characterized in that, The hydrophobic silica aerogel powder has a particle size of 5–15 μm and a specific surface area of 600–800 m². 2 / g, thermal conductivity ≤0.022 W / (m·K).
4. The method for preparing a low thermal conductivity aerogel composite foamed silicone cotton according to claim 1, characterized in that, The reinforcing filler is fumed silica, the flame retardant filler is aluminum hydroxide, the structuring control agent is hydroxyl silicone oil, and the reaction inhibitor is ethynylcyclohexanol.
5. The method for preparing a low thermal conductivity aerogel composite foamed silicone cotton according to claim 1, characterized in that, The molecular weight of the vinyl polysiloxane is 500,000 to 700,000, the viscosity of the low-viscosity vinyl silicone oil is 100 to 1000 mPa·s, and the active hydrogen content of the hydrogen-containing silicone oil is 1.0% to 1.5%.
6. The method for preparing a low thermal conductivity aerogel composite foamed silicone cotton according to claim 1, characterized in that, After the vulcanization is completed, the semi-finished product is placed in a shaping fixture and kept at a constant temperature for 1.5 to 3 hours to eliminate the internal stress of molding.
7. The method for preparing a low thermal conductivity aerogel composite foamed silicone cotton according to claim 1, characterized in that, Both the reinforcing filler and the flame-retardant filler are subjected to hydrophobic modification treatment.
8. An application of a low thermal conductivity aerogel composite foamed silicone cotton, characterized in that, The aerogel composite foamed silicone cotton is prepared by the method of any one of claims 1-7, and the aerogel composite foamed silicone cotton is used as a heat insulation and sealing material in power battery PACK, energy storage cabinet or new energy electrical equipment.